2020
DOI: 10.1177/2333721420965819
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Elder Abuse Forensic Nurse Examiner e-Learning Curriculum

Abstract: In Ontario, Canada, there is a need for an easily accessible training for forensic nurse examiners on the provision of care for abused older adults. In this study, our objective was to develop and evaluate a novel elder abuse nurse examiner e-learning curriculum focused on improving the care provided to older adults. The curriculum was launched on an online learning management system to forensic nurses working across Ontario’s hospital-based violence treatment centers in June 2019 and evaluated using pre- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The authors clarified that education might give an incentive to document the incidence [ 5 , 21 ]. Along similar lines, other studies revealed that reporting on elder abuse increased after attending educational training that consisted of lectures, simulation lab, and debriefings [ 4 , 6 , 17 , 26 , 28 ]. Additionally, participants stated that after receiving the education they felt confident in reporting the cases of elder abuse [ 4 ].…”
Section: Prisma Flow Diagrammentioning
confidence: 60%
See 4 more Smart Citations
“…The authors clarified that education might give an incentive to document the incidence [ 5 , 21 ]. Along similar lines, other studies revealed that reporting on elder abuse increased after attending educational training that consisted of lectures, simulation lab, and debriefings [ 4 , 6 , 17 , 26 , 28 ]. Additionally, participants stated that after receiving the education they felt confident in reporting the cases of elder abuse [ 4 ].…”
Section: Prisma Flow Diagrammentioning
confidence: 60%
“…As suggested by previous studies, there is a positive relationship between training and education for nurses in elder abuse, and reporting and reduction in cases [ 3 , 6 , 20 , 21 ]. On this note, there is evidence to suggest that participants who were victimized would prefer a specialized nurse in detecting and managing their case [ 22 ].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations